Paleoclimatology : reconstructing climates of the quaternary - Bradley, Raymond S., 1948- (Amsterdam ; Boston : Elsevier, 2015)
"Paleoclimatology: Reconstructing Climates of the Quaternary, Third Edition, provides a thorough overview of the methods of paleoclimatic reconstruction and of the historical changes in climate during the past three million years. This thoroughly updated and revised edition systematically examines each type of proxy and elucidates the major attributes and the limitations of each. Paleoclimatology, Third Edition provides necessary context for those interested in understanding climate changes at present and how current trends in climate compare with changes that have occurred in the past. The text is richly illustrated and includes an extensive bibliography for further research."-- c provided by publisher.
Paleoclimatic reconstruction -- Climate and climatic variation -- Dating methods 1 -- Dating methods 2 -- Ice cores -- Marine sediments -- Loess -- Speleothems -- Lake sediments -- Nonmarine geologic evidence -- Insects and other biological evidence from continental regions -- Pollen -- Tree rings -- Corals -- Historical documents -- Appendix A: further considerations on radiocarbon dating -- Appendix B: Internet resources in paleoclimatology.
Includes bibliographical references (pages 559-665) and index.
Keywords: Paleoclimatology -- Quaternary; Geology, Stratigraphic -- Quaternary